A study of some economic traits in a herd of Kenana cattle. Service period, calving interval and gestation period - Khalafallah, A.M.; Khalifa, H.A.A. (1983)
The reproduction of the Kenana cattle was studied to establish the service period (SP), calving interval (CI) gestation period (GP), and economic production characteristics. Age of cow had significant effect on SP and highly significant effect on calving interval. The variations in the SP and in the CI were due to non-genetic factors which could be improved through management.